2015
DOI: 10.1111/apt.13380
|View full text |Cite
|
Sign up to set email alerts
|

Treating ischaemia‐reperfusion injury with prostaglandin E1 reduces the risk of early hepatocellular carcinoma recurrence following liver transplantation

Abstract: SUMMARY BackgroundSurgical stress by hepatic ischaemia-reperfusion (I/R) is supposed to promote intra-and extrahepatic tumour recurrence. Treatment with prostaglandin E1 (PGE1) has been shown to attenuate hepatic I/R injury in liver transplant patients, but the potential anti-cancer effects have not been analysed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 43 publications
0
32
0
Order By: Relevance
“…The results of the present study point toward the importance of strategies aimed to decrease IRI particularly for patients within the standard selection criteria. A single retrospective study revealed decreased magnitude of IRI, as illustrated by low transaminase levels and decreased risk of HCC recurrence in patients receiving prostaglandin E1 analog alprostadil in the early period after liver transplantation 33 . The protective effects of ischemic preconditioning with respect to the development of metastases were also reported in a recent experimental study 14 .…”
Section: Discussionmentioning
confidence: 99%
“…The results of the present study point toward the importance of strategies aimed to decrease IRI particularly for patients within the standard selection criteria. A single retrospective study revealed decreased magnitude of IRI, as illustrated by low transaminase levels and decreased risk of HCC recurrence in patients receiving prostaglandin E1 analog alprostadil in the early period after liver transplantation 33 . The protective effects of ischemic preconditioning with respect to the development of metastases were also reported in a recent experimental study 14 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, rate of early HCC relapse within 1 year from LT was significantly higher without PGE1 treatment (34% vs. 5.1%; P < 0.001). When stratified according the MC, PGE1-therapy did not exert an independent prognostic impact in Milan In, whereas it was identified as a significant and independent promoter of RFS in patients with MC Out patients (HR = 5.09; 95%CI 1.64-15.76; P = 0.005) [114] .…”
Section: Improving Cancer-specific Outcome By Mitigating I/r Injurymentioning
confidence: 85%
“…In a retrospective clinical analysis, our transplant group was able to demonstrate that early post-LT treatment with prostaglandin E1 (PGE1) reduces hepatic I/R damage and provides beneficial immunomodulatory capabilities, finally improving cancer-specific outcome [114] . In a series of 106 HCC LT patients, RFS rates at 3-and 5-year post LT were significantly better in the PGE1-treatment group (87.9%; 85.7%) compared to the non-PGE1 subset (65.3%; 63.1%; P = 0.003).…”
Section: Improving Cancer-specific Outcome By Mitigating I/r Injurymentioning
confidence: 99%
“…2 Letter: cytomegalovirus colitis in a patient treated with ipilimumab for metastatic melanoma and we would like to report the case of a patient developing bloody diarrhoea after treatment with ipilimumab for metastatic melanoma.…”
Section: Acknowledgementmentioning
confidence: 99%
“…2 It works by prolonging T-cell activation, resulting in augmented host T-cell immunity and sustained immune response against tumour cells due to loss of tolerance. This immune dysregulation is associated with several immune-related adverse events including dermatitis, endocrinopathies, uveitis, hepatitis and colitis.…”
Section: Acknowledgementmentioning
confidence: 99%